Personalization of Instruction: Design Dimensions and Implications for Cognition. Issue 1 (2nd January 2018) - Walkington, Candace; Bernacki, Matthew L.
ABSTRACT: Instruction can be made relevant to students when it draws upon and utilizes their interests, experiences, and "funds of knowledge" in productive ways to support classroom learning. This approach has been referred to as "context personalization." In this paper, we discuss the cognitive basis of personalization interventions, including theories related to grounding via concrete experience, activation of funds of knowledge, and cognitive load. We discuss a series of interventions in which different approaches to personalization, each of which involves a different operationalization of how instruction can be made "relevant, " are compared in studies of mathematics learning, often involving intelligent tutoring systems. We show how results vary for these interventions based on the degree to which personalization is designed to match with and draw upon learners' unique quantitative experiences, based on prior cognitive characteristics of learners and based on the degree of ownership and control students experience in the learning environment.